High activity copper catalyst for one‐step conversion of methanol to methyl formate at low temperature - Rao V.M.; Shankar V. (My University, 2025)
Dehydrogenation of methanol on copper catalysts supported on SiO2 and modified by Cr2O3 was studied in the temperature range of 200 to 270°C. The chief product of reaction was methyl formate together with carbon monoxide and traces of formaldehyde. It was found that very high and sustained activity could be achieved by the method adopted for preparation of the catalysts. The unused catalyst was completely amorphous, but in catalyst samples used for long periods of time the presence of crystallites in the size range 50 to 65 Å was observed. Nearly 80% of theoretically obtainable conversion of methanol to methyl formate was achieved in laboratory scale tubular reactor. A catalyst containing Cu:Cr2O3:SiO2 = 5.0:5.90:7.0 prepared by the method described proved to be very active at low temperatures, giving 41% conversion to methyl formate at 230°C for long periods of use. No interaction between the active component and the support was noticeable. Addition of chromia improved the catalyst texture and stability. When nickel was present in quantities less than 1.25%, it acted as a promoter and gave improved performance. Copyright © 1988 Society of Chemical Industry